Product Benchmarking Using DFA and DFD Tools / Amir Reza Akhiani - Amir Reza, Akhiani (2013)
Tight competition between manufacturers forces them to look for new ways to increase productivity and quality and hence reduce costs. These efforts have led researchers to develop methods such as the DFX Tools: Design for Manufacturing, Design for Assembly, Design for Disassembly, Design for Environment, Design for Recyclability, etc. In this research, Design for Assembly (DFA) and Design for Disassembly (DFD) methods are used to analyze and optimize an automotive product. DFA reduces time and cost through parts reduction, which simplifies assembly and increases reliability. DFD reduces cost by hastening the recycling or dismantling processes (direct effect) and decreases environmental impact and damage to the environment (indirect effect). Most big manufacturing companies such as Sony, Hitachi, Ford, and Chrysler have their own method for implementing DFA and DFD, which are developed for a specific product. One of the oldest and general methods for DFA and DFD is the Boothroyd Method. The main goal of this research is to optimize assembly of the rear light of Proton Waja cars through supply of the assembly data to the DFA and DFD software, and to implement the software’s recommendations into improving the initial design. When compared with the old design, the new design markedly improves assembly, as shown by the DFA index and cost breakdown graph. The software considers only the cost reduction that is due to parts reduction; costs of producing new parts such as molds for the plastic parts or stamping die for the metallic parts were not considered.